The Impact of Polymers on Enzalutamide Solid Self-Nanoemulsifying Drug Delivery System and Improved Bioavailability - Su-Min Lee; Jeong-Gyun Lee; Tae-Han Yun; Chul-Ho Kim; Jung-Hyun Cho; Kyeong-Soo Kim (MDPI AG, 2024)
Enzalutamide (ENZ), marketed under the brand name Xtandi® as a soft capsule, is an androgen receptor signaling inhibitor drug actively used in clinical settings for treating prostate cancer. However, ENZ's low solubility and bioavailability significantly hinder the achievement of optimal therapeutic outcomes. In previous studies, a liquid self-nanoemulsifying drug delivery system (L-SNEDDS) containing ENZ was developed among various solubilization technologies. However, powder formulations that included colloidal silica rapidly formed crystal nuclei in aqueous solutions, leading to a significant decrease in dissolution. Consequently, this study evaluated the efficacy of adding a polymer as a recrystallization inhibitor to a solid SNEDDS (S-SNEDDS) to maintain the drug in a stable, amorphous state in aqueous environments. Polymers were selected based on solubility tests, and the S-SNEDDS formulation was successfully produced via spray drying. The optimized S-SNEDDS formulation demonstrated through X-ray diffraction and differential scanning calorimetry data that it significantly reduced drug crystallinity and enhanced its dissolution rate in simulated gastric and intestinal fluid conditions. In an in vivo study, the bioavailability of orally administered formulations was increased compared to the free drug. Our results highlight the effectiveness of solid-SNEDDS formulations in enhancing the bioavailability of ENZ and outline the potential translational directions for oral drug development.